A metodologia de análise e solução de problemas baseada no modelo de gestão da qualidade total: um modelo de automação e análise - Adriano Beltrao Clary (1997)
The method of management based on PDCA is showed, placed on global context of the Total Quality management and aim to an analysis about the aspects like his evolution and potentialities. A data base system was developed based on the abovementioned methodology and, to do this, was used the Microsoft Visual Basic 3.0 programming language in a DOS/WINDOWS platform. This data base system show us, between another points, the fact that it would be a reference to professionals or begnner´s sudents of the Total Quality theory, and, at the same time, to facilitate the project´s standardization which was developed by expertness professionals in this management model. Following the premise of effectiveness on the whole method application, was made a analysis about it and about tools, who are nowadays applied whit in and with potentialities to be applied